(untitled) - Food and Agriculture Oganization of United Nations (Rome, 2008)
FAO Workshop on Vulnerable Ecosystems and Destructive Fishing in deep-sea fisheries examined available information on national, institutional personal experiences in ralation to this issue. Relevant ecological aspects were reviewed and suggestions as how to consider these issues in terms of International Guidelines for the Management of Deep-sea Fisheries in the High Seas were disscused and documented.
Keywords: Deep-sea fisheries,Ecosystems,Nghề cá biển sâu,Hệ sinh thái